2014
DOI: 10.1093/toxsci/kfu026
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Preclinical Photosafety Testing Strategy for Systemically Applied Pharmaceuticals

Abstract: Phototoxic properties of systemically applied pharmaceuticals may be the cause of serious adverse drug reactions. Therefore, a reliable preclinical photosafety assessment strategy, combining in vitro and in vivo approaches in a quantitative manner, is important and has not been described so far. Here, we report the establishment of an optimized modified murine local lymph node assay (LLNA), adapted for phototoxicity assessment of systemically applied compounds, as well as the test results for 34 drug candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The in vivo and ex vivo studies may be useful as predictors but the reliability of these is not high in that often a positive signal in, for example, the 3T3 neutral red assay in vitro, does not necessarily indicate that a drug will be phototoxic when used clinically. The 3T3 neutral red assay is accepted as the standard preclinical method of in vitro testing for drug phototoxicity (139) and the photocomet assay for evidence of DNA damage (140). Indeed, pre-clinical in vitro non-animal phototoxicity and photoallergy testing may be employed in photosafety evaluation, with endeavours to improve specificity and sensitivity and in certain settings may minimise the need for animal and human studies (141).…”
Section: Regulatory Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vivo and ex vivo studies may be useful as predictors but the reliability of these is not high in that often a positive signal in, for example, the 3T3 neutral red assay in vitro, does not necessarily indicate that a drug will be phototoxic when used clinically. The 3T3 neutral red assay is accepted as the standard preclinical method of in vitro testing for drug phototoxicity (139) and the photocomet assay for evidence of DNA damage (140). Indeed, pre-clinical in vitro non-animal phototoxicity and photoallergy testing may be employed in photosafety evaluation, with endeavours to improve specificity and sensitivity and in certain settings may minimise the need for animal and human studies (141).…”
Section: Regulatory Requirementsmentioning
confidence: 99%
“…Photosensitivity to topical agents is often investigated in animal models of skin reactions and also in a murine local lymph node assay (LLNA) and may also be adapted for use in the investigation of the phototoxic potential of systemically delivered compounds. This appears to have supportive utility in the preclinical photosafety assessment of potentially phototoxic drugs, based on establishing a photoirritation factor, which in turn may help to triage those drugs that need to go on to testing in the human setting (139).…”
Section: Regulatory Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…3T3 NRU test is only being employed for hazard identification while its utility for the assessment of phototoxic potency is not warranted.In particular, this assay system lacks metabolic activity which is critical in the manifestation of systemically exposed chemicals. Therefore, for systemically exposed chemicals that require metabolic activation like monocrotaline, riddelliine, and heliotrine (pyrrolizidine alkaloids) (28) , in vivo animal studies are recommended (5 , 29) .…”
Section: Test Methods For Phototoxicity and Animal Alternativesmentioning
confidence: 99%
“…The current strategy of our method is to predict the photoallergic response qualitatively by comparing the dermal response between the UV+ and UV– groups applied with the test chemical in selected dose expected to cause no or minimal sensitization potential (equal or less than EC3) without a phototoxic response under the standard LLNA protocol. Schumann et al () reported a photosafety evaluation approach based on multiple dose groups using the lowest‐observed‐adverse‐effect level and NOAEL. This approach may achieve the quantitative evaluation of the photoallergic potential of chemicals.…”
Section: Discussionmentioning
confidence: 99%